Atomic structure of chlorine containing calcium silicate glasses by neutron diffraction and 29Si solid‐state NMR. (4th July 2017) - Forto Chungong, Louis; Swansbury, Laura A.; Mountjoy, Gavin; Hannon, Alex C.; Lee, Adam F.; Martin, Richard A.
Abstract: Bioactive glasses are of great importance for medical and dental applications. In order to understand, model, and predict the behavior of these materials, and ultimately improve their design, it is important to understand the structure of these glasses. Ion dissolution is known to be the crucial first step in bioactivity and is strongly dependent upon the atomic‐scale structure and network connectivity. While significant progress has been made understanding the structure of oxide‐based glasses, relatively little is known about the structure of bioactive glasses containing halides. Recently, a series of novel chloride‐based bioactive glasses has been developed. Chlorapatite converts to hydroxyapatite in water and these glasses are therefore of interest for novel toothpastes. This study reports the first detailed structural investigation of these bioactive chloride glasses using neutron diffraction and solid‐state NMR. Chlorine was found to bond to calcium within the glass, and no evidence of Si‐Cl bonding was detected. Furthermore, the absence of a chemical shift in the 29 Si NMR upon the addition of CaCl2 helped confirm the absence of detectable amounts of Si‐Cl bonding. Given that chlorine does not disrupt the Si‐O‐Si network, widely used network connectivity models are therefore still valid in oxychloride glasses.